ANALISIS PENDAPATAN DAN EFISIENSI EKONOMI RELATIF USAHATANI KEDELAI PADA PROGRAM SEKOLAH LAPANG PENGELOLAAN TANAMAN TERPADU (SLPTT) - Titin Agustina (STIE Mandala Jember, 2013)
Soybean is one of the important food commodity’s after rice which has a strategic position in the overall national food policy because its role is critical in Indonesia food menu resident. Needs of the community and soybean processing industry tend to increased from year to year has not been matched by theavailability of sufficient soy because soy production in the domestic remains low. The constraints of national soybean production increased many faces, one of which is the low productivity of soybean. The low productivity because most farmers do not use quality seed varieties and crop management techniques arestill not optimal. One of the main program the Ministry of Agriculture relating to technological innovation as an effort to increase production of food cropsincluding soybeans is PTT (Integrated Crop Management) approach and is done through SLPTT (Integrated Crop Management Field School). However, theimplementation is still faced many obstacles, mainly in terms of farming techniques that lead to the production and productivity of soybean at the farm level is relatively low so the income of farmers is also low. The objective of this study was to analyze how far the Integrated Crop Management Field School (SLPTT) Program can increase farmers income. The farmer population under study is divided into two, namely the participant farmers of SLPTT Program and farmers are not participants of SLPTT Program. By using the Unit Output Price Cobb-Douglas’s profit function obtained conclusion that SLPTT Program can increase farmers income. The factors that affect negatively and significantly to the income are the price of seed,the price of fertilizer, the prices of pesticides and the wage of labor, while the factor that affect positively and significantly to the income is land size. Soybean farm of SLPTT farmers are more efficient economically than non SLPTT soybean farmers.